Perspectives on isolation: the relation of narrative technique to theme in selected works by Joseph Conrad - Gaylard, Robin Peter (Rhodes University, Faculty of Humanities, Department of Literary Studies in English)
" ... the central concern of this thesis, which is to investigate the ways in which Conrad uses a particular technique (that of the first-person narrator ) to focus our attention, to secure our involvement, and to direct our sympathies. At the same time I wish to examine the extent to which the central themes or concerns of each work derive from the interaction between the narrator and the man whose experience he confronts, from "the challenging interplay of two frames of reference, two schemes of values, two sets of attitudes" that the use of a dramatized narrator makes possible." (Introd., p. 5),Adobe Acrobat 9.53 Paper Capture Plug-in
Keywords: Conrad, Joseph, 1857-1924